Simplifique a expressão : x=secx-Cosx/Cossecx-senx
Resposta:tg^3x
Soluções para a tarefa
Respondido por
2
A = sec(x) - cos(x)/ coss(x) - sen(x)
A = 1/cos(x) - cos(x)/1/sen(x) - sen(x)
A = 1 - cos^2(x)/cos(x) / 1 - sen^2(x)/sen(x)
A = [1 - cos^2(x)].sen(x)/ [1 - sen^2(x)].cos(x)
A = sen^2(x).sen(x)/cos^2(x).cos(x)
A = sen^3(x)/cos^3(x)
A = tg^3(x)
A = 1/cos(x) - cos(x)/1/sen(x) - sen(x)
A = 1 - cos^2(x)/cos(x) / 1 - sen^2(x)/sen(x)
A = [1 - cos^2(x)].sen(x)/ [1 - sen^2(x)].cos(x)
A = sen^2(x).sen(x)/cos^2(x).cos(x)
A = sen^3(x)/cos^3(x)
A = tg^3(x)
Perguntas interessantes
Biologia,
11 meses atrás
Ed. Física,
11 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás